Special Relationship Between the United Kingdom and the United States of America in the Light of Brexit and Donald Trump's Victory in the Presidential Election - Danel, Łukasz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
This article is devoted to the "special relationship" between the United Kingdom and the United States: a strategic partnership that has united these two countries for good after WWII, even though in many respects it has lasted since the first half of the 19th century. The author starts with presenting the historic outline of the "special relationship" with an emphasis on the characteristics of mutual ties and dependencies. The author also analyses the political circumstances in which tightening or loosening of the British and American relations took place. In the final part of the article, the author refers to the most recent political events, which in 2016 took place in Great Britain and in the United Sates. In this manner, the author is trying to answer the question on how the decision on leaving the European Union by Great Britain (the so-called Brexit) and the election of Donald Trump as the US president will influence the shape of the British and American alliance